Spectroscopic studies of Er-doped Si-rich silicon oxide/SiO2 multilayers - Gourbilleau, Fabrice; Dufour, Christian; Madelon, Roger; Rizk, Richard (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
The effects of Si nanocluster (Si-nc) size and of the distance between Si-nc and Er ion on the photoluminescence of the Er3+ ions have been investigated by means of appropriate multilayer configurations fabricated by reactive magnetron sputtering. On the one hand, the effect of Si-nc size is studied in Er-Si-rich SiO2/SiO2 multilayers. The coupling between Si-nc and Er3+ ions is found to be less efficient when the Si-nc’s reach a size of 5 nm and attributed to a loss of the quantum confinement of carriers. On the other hand, the interaction distance between Si-nc and Er ions is determined through the photoluminescence properties of Si-rich SiO2/Er-SiO2 multilayers. The characteristic interaction distance Si-nc-Er is dependent on the nature of the sensitizers with 0.4 ± 0.1 nm for amorphous Si and 2.6 ± 0.4 nm for Si nanocrystals.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 21-30
Keywords: optyka; reactive magnetron sputtering; multimayers; erbium; Si nanoclusters; photoluminescence; interaction distance